PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK KEPALA BERNOMOR TERSTRUKTUR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 10 PADANG - Yusdario, Budi; K, Delsi; Melisa, Melisa (Pendidikan Matematika, 2014)
ABSTRACTÂ This research was designed for determining whether the mathematics conceptual understanding of students taught by using technique Numbered Head of Structured cooperative learning was better than that of students taught by using conventional learning. This was an experimental Â research wich used pre eksperimental design: static group comparison. The data was collected by using a on posttest mathematics conceptual understanding. The results of hypothesis test showed that P-value=0,000 was smaller than Î±=0,05, indicating that the hypothesis was accepted. Thus, it was concluded that the mathematics conceptual understanding of students taught by using technique Numbered Head of Structured cooperative learning was better than that of students taught by using conventional learning of SMPN 10 Padang.